Taking Management Digital : Lessons from the Development of an Innovative Management Information System for Small Businesses in Ethiopia - Alibhai, Salman; Strobbe, Francesco; Villanger, Espen (World Bank, Washington, DC, 2018)
In many aid projects, monitoring and evaluation is a static exercise driven by donor reporting requirements. After project closure, there are seldom sustainable benefits of the monitoring and evaluation system. This paper examines how monitoring and evaluation can be transformed into a dynamic tool for effective project management, with benefits carrying over beyond the typical project lifecycle. The paper assesses an innovative, digital management information system developed under the Women Entrepreneurship Development Project, a Government of Ethiopia initiative financed by a World Bank International Development Association loan and grant funding from Global Affairs Canada. The paper examines the context of the development of the management information system, its effectiveness, and its potential for sustainability. Ethiopia is among the poorest countries in the world, and government administration units involved in administering projects often face funding and resource shortfalls. The paper demonstrates how effective and sustainable monitoring and evaluation systems can be developed even in challenging contexts such as these, by focusing on simple technical solutions that can be maintained and refined locally, ensuring low development and maintenance costs compatible with government monitoring and evaluation budgets, and linking project-level monitoring and evaluation to broader government operations.